ANALISIS JARINGAN SOSIAL PADA AKTOR PENGELOLAAN SAMPAH DI DESTINASI PARIWISATA KABUPATEN BANYUWANGI - Dimas Teguh Prasetyo; Zuli Rhodiyah; Rifka Annisa (Jurnal Pariwisata Pesona, 2021)
The development of tourism in Indonesia is like a double-edged sword. One side is able to improve the economy and welfare of the community around tourist destinations. However, on the other hand, it has the potential to generate new waste generation from tourism activities. It needs support from all parties to be able to realize integrated and comprehensive waste management. A qualitative study using social network analysis was conducted in Banyuwangi Regency. Researchers identify relationships between actors related to waste management around tourist destinations. About 21 people from academia, community, general public, local government and entrepreneurs took part in this study. Data collection was carried out using an online questionnaire containing demographic data and 10 questions regarding 5 aspects of solid waste management, namely regulation, institutions, funding, multi-stakeholder participation and technical operations. The results of the social network analysis show that local governments are actors who are assumed to have an important role in the aspects of regulation, institutions, funding and multi-stakeholder participation. In addition, community organizations, academics and businessmen encourage local governments to be able to implement strategic steps for waste management in tourist destinations. This study has implications for the importance of all parties to begin to realize their role in waste management in tourist destinations. However, a collaboration and synergy also need to understand the potential challenges and conflicts of interest between actors